Pengembangan Gim Edukasi Pembelajaran IQRA-1 dan Tajwid menggunakan Augmented Reality - Andri Alfian; Eriq Muhammad Adams Jonemaro; Muhammad Aminul Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Studying, understanding and practicing Qur'an is an obligatory thing that every Muslim does in his daily life. However, for now, the method of learning Qur'an at the basic level still uses conventional methods, one of which is the IQRA theory method, which is less favored by students in learning hijaiyah letters. This problem can be dealt by utilizing technology which is currently easy to use by various age groups, especially children. Learning media can also includes gamification aspects, such as levels and scores to create more interesting learning ecosystem. In addition, Augmented Reality technology that can display digital information to the real world is also starting to be widely applied to create immersiveness to the use of edutainment media. Therefore, the AR-IQRA-1 and Tajwid game was created, which packages IQRA learning techniques in a more interactive, interesting and modern way, as an option for more modern learning method, to increase interest in learning the pronunciation of Hijaiyah letters. AR-IQRA-1 and Tajweed game is developed with AR technology using markerless method that brings up 3D images of the hijaiyah letters. The development of the AR-IQRA-1 and Tajweed game uses methods including needs analysis, design, implementation, and testing. Functional testing of AR-IQRA-1 and Tajweed game resulted in 4 kinds of functions that were declared fulfilled with an overall valid logic structure. The usability testing of AR-IQRA-1 and Tajweed game being held using the System Usability Scale (SUS) technique with 24 student respondents, obtained a result of 81.04 which means that AR-IQRA-1 and Tajweed Game has acceptable criteria and grade B with an excellent rating.